Poverty Level and Conflicts Over Money Within Families - Herien Puspitawati (Media Gizi dan Keluarga, 2003)
The Depression of the 1930s was followed ahalf century later by the depression of the 1980s.Voydanoff (1990) noted that the restructuring ofthe American economy during the late 1980s wasaccompanied by increasing le\.els of economicdistress. Aspects of economic distress, includingemployment instability, emplo~ment uncertainty,economic deprivation, and economic strain havebeen found to be related to individual adjustmentand family relations. Thus. changes in theeconomy during the 1980s ha1.e resulted inchanges in family life (Voydanoff, 1990). Forexample, McVeigh and Shostak ( 1978) reportedthat poverty is associated with a lack of decenthousing and an inadequate diet Other correlatesof poverty include low educational attainment anda lack of proper medical care.